1980
DOI: 10.1038/283383a0
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour of tsetse flies infected with salivarian trypanosomes

Abstract: Although much is known about factors which determine infection rates of salivarian trypanosomes (subgenera Nannomonas, Duttonella and Tryanozoon) in the tsetse fly Glossina, it is not clear why infection rates of Trypanozoon are high in mammalian hosts but low in wild-caught Glossina and why trypanosomiasis occurs where Glossina is not readily detectable. We report here that the feeding behaviour of trypanosome-infected Glossina differed from that of uninfected control flies. Infected flies probed more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 13 publications
2
51
2
Order By: Relevance
“…The plague bacterium Yersinia pestis, transmitted by the tropical rat £ea Xenopsylla cheopis, blocks the proventriculus of the £ea and causes regurgitation when the £ea is blood feeding (Bacot & Martin 1914). Trypanosomes can a¡ect the mechanoreceptive sensilla of their tsetse £y hosts, so that infected £ies probe more frequently than uninfected £ies (Jenni et al 1980;Roberts 1981). As parasites are frequently transmitted during probing, transmission is likely to be increased.…”
Section: Introductionmentioning
confidence: 99%
“…The plague bacterium Yersinia pestis, transmitted by the tropical rat £ea Xenopsylla cheopis, blocks the proventriculus of the £ea and causes regurgitation when the £ea is blood feeding (Bacot & Martin 1914). Trypanosomes can a¡ect the mechanoreceptive sensilla of their tsetse £y hosts, so that infected £ies probe more frequently than uninfected £ies (Jenni et al 1980;Roberts 1981). As parasites are frequently transmitted during probing, transmission is likely to be increased.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas in some investigations infected flies probed three times more often than non-infected flies and needed more time for blood ingestion (e.g. Jenni et al, 1980), these effects could not be observed in other investigations (Makumi and Moloo, 1991). Strong effects have been observed in another trypanosomatid group, the Leishmania.…”
Section: Occurrence Of Parasitogenic Changes Of Vector Behaviourmentioning
confidence: 65%
“…Some salivarian trypanosomatids develop carpets of flagellates in the foregut. Since the capacity of the cibarial pump cannot be increased indefinitely, this might reduce the blood speed (Jenni et al, 1980). Much stronger reductions of the diameter are known for Leishmania-infected phlebotomines and Yersinia pestis-infected rat fleas.…”
Section: Effects On Feeding Behaviourmentioning
confidence: 97%
See 1 more Smart Citation
“…In tsetse-fly-trypanosome associations, many studies have now demonstrated that infected flies increase the probing rate and feed more voraciously than uninfected flies (e.g. Hurd, 2003;Jenni et al, 1980;Lefèvre and Thomas, 2008;Molyneux and Jefferies, 1986;Roberts, 1981). Two parasito-proteomics studies were done on two insect-vector-parasite associations to improve understanding of the proximate cause(s) leading to the alteration of the insect vector behaviour: (1) the mosquito Anopheles gambiae Giles (Diptera, Culicidae) parasitized by a malaria parasite, Plasmodium berghei (Haemosporida, Plasmodiidae) (Lefèvre et al, 2007a), and (2) the tsetse fly Glossina palpalis gambiensis (Vanderplank) (Diptera, Glossinidae), parasitized by the sleeping sickness parasite, Trypanosoma brucei brucei (Kinetoplastida, Trypanosomatidae) (Lefèvre et al, 2007b).…”
Section: Insect-vector-parasite Associationsmentioning
confidence: 99%